2021
DOI: 10.1007/s13668-021-00370-4
|View full text |Cite
|
Sign up to set email alerts
|

How Does Fasting Affect Cognition? An Updated Systematic Review (2013–2020)

Abstract: Introduction:The goal of this review was to provide an update on the literature examining how voluntary, temporary abstention from eating impacts cognitive function. Methods and Results:We evaluated peer-reviewed articles published between August 2013 and January 2021 that assessed adults, included a measure of cognitive functioning with neutral stimuli, and compared individuals in a fasted state to individuals in a fed state (either within-or between-subject designs). Nineteen articles (21 studies) met inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…One plausible hypothesis may be that the periodic restoration of energy balance, for example, through periods of lesser restriction, may increase cognitive flexibility. Consistent with this interpretation, literature from other areas such as the impact of intermittent fasting on cognition has suggested the existence of cognitive effects in experiemental settings when manipulating fasting (Benau et al, 2021). It is notable that while both ANR and ANBP are characterized by overall low body weight and fat mass, this is not necessarily the case in atypical AN, which presents the same restrictive and rigid patterns as AN, as well as significant weight loss, but not objectively low weight (Forney et al, 2017).…”
Section: Respective Roles Of Low Body Weight Low Fat Mass Weight Supp...mentioning
confidence: 77%
See 2 more Smart Citations
“…One plausible hypothesis may be that the periodic restoration of energy balance, for example, through periods of lesser restriction, may increase cognitive flexibility. Consistent with this interpretation, literature from other areas such as the impact of intermittent fasting on cognition has suggested the existence of cognitive effects in experiemental settings when manipulating fasting (Benau et al, 2021). It is notable that while both ANR and ANBP are characterized by overall low body weight and fat mass, this is not necessarily the case in atypical AN, which presents the same restrictive and rigid patterns as AN, as well as significant weight loss, but not objectively low weight (Forney et al, 2017).…”
Section: Respective Roles Of Low Body Weight Low Fat Mass Weight Supp...mentioning
confidence: 77%
“…Preliminary work examining state negative energy balance examined the effect of 48 h fasting on cognition in amateur weight lifters (Solianik et al, 2016). Findings revealed that fasting increased performance on cognitive flexibility tasks, rather than the contrary, although not all studies in this area have reported consistent findings (Benau et al, 2014; Benau et al, 2021). Of note, however, the participants in this study were not diagnosed with MD, and it is important not to generalize the findings to clinical groups (Rodgers & Murray, 2022).…”
Section: Implications For Other Disorders: Cognitive and Behavioral R...mentioning
confidence: 82%
See 1 more Smart Citation
“…Importantly, in literature, the findings on the effects of fasting duration on cognitive performance are inconsistent. Some studies have demonstrated fasting effects already after 10–12 h fasting (Ginieis et al, 2018 ; Macpherson et al, 2015 ), whereas others utilized much longer fasting protocols ranging up to 48 h (Solianik, et al, 2020 , see Benau et al, 2021 for review). Regarding cognitive flexibility, results showed that hunger had no effect following 5 h fasting (Piech et al, 2009 ), but lead to performance impairment after 16 h (Bolton et al, 2014 ) and after 18 h (Pender et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers observed psychological changes that were similar to symptoms of AN as well as cognitive changes (including loss of concentration) but did not investigate neuropsychological performance. Newer research investigating cognitive consequences of restricted food intake in healthy individuals has only focused on short-term fasting (3–48 h) [ 11 ]. Preliminary evidence from a systematic review [ 11 ] suggested that short-term fasting is associated with executive function deficits.…”
Section: Introductionmentioning
confidence: 99%